ESTIMASI POPULASI ORANGUTAN DI AREAL REKLAMASI PERTAMBANGAN BATUBARA DI KUTAI TIMUR, KALIMANTAN TIMUR - Liza Niningsih (Fakultas Pertanian, 2022)
Orangutans (Pongo spp.) are currently found only on the islands of Sumatra and Borneo. Bornean orangutan (Pongo pygmaeus) face a high risk of extinction due to almost 80% of the distribution of orangutans in Kalimantan occurs outside of conservation areas. Orangutans are also found in the Coal Mining Rehabilitation Area called ARPB in Sangatta, East Kutai, East Kalimantan. The objective of this research was to estimate the orangutan population living in ARPB in Sangatta. Data collection used direct observation to orangutan found in ARPB. This study has found 41 orangutans in ten ARPBs covering an area of 912.29 ha, from November 2013 to January 2015. The orangutans found consists of 17.07% of adult males, 39.02% of adult females, 12.20% of juveniles, 9.76% of children, and 21.95% of infants. This was an indication of the success of orangutans’ adaptation in the coal mining area, especially in ARPB. The fact about population and demographic structure of orangutans in ARPB leads to indications of the success of orangutans in adapted in ARPB.